UAF1 deubiquitinase complexes facilitate NLRP3 inflammasome activation by promoting NLRP3 expression - Hui Song (Nature Portfolio, 2020)
NLRP3 inflammasome activation is regulated by various signaling pathways to ensure inflammation does not go unchecked. Here the authors show how deubiquitination avoids this regulation to activate the NLRP3 inflammasome through the function of UAF1/USP deubiquitinase complexes.